2013
DOI: 10.1111/medu.12234
|View full text |Cite
|
Sign up to set email alerts
|

Associations between residency selection strategies and doctor performance: a meta-analysis

Abstract: OBJECTIVES The purpose of this study was to use meta-analysis to establish which of the information available to the resident selection committee is associated with resident or doctor performance.METHODS Multiple electronic databases were searched to 4 September 2012. Two reviewers independently selected studies that met the present inclusion criteria and extracted data in duplicate; disagreement was resolved by consensus. Risk for bias was assessed using a customised bias assessment tool. Measures of associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
73
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 97 publications
0
73
2
4
Order By: Relevance
“…Particularly strong associations have been found between USMLE scores and other exam-related measures of success, such as scores on in-training examinations in specialties such as dermatology [7], emergency medicine [8], general surgery [9], and neurology and neurosurgery [10], as well as across specialties in meta-analyses [11,12]. Other positive associations were found between USMLE scores and a resident’s likelihood of successfully passing board examinations [12,13], especially on the first attempt [14,15]. On the other hand, USMLE scores tend to not be as strongly correlated with more subjective outcome measures, such as supervisor and faculty evaluations [10,11,15].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly strong associations have been found between USMLE scores and other exam-related measures of success, such as scores on in-training examinations in specialties such as dermatology [7], emergency medicine [8], general surgery [9], and neurology and neurosurgery [10], as well as across specialties in meta-analyses [11,12]. Other positive associations were found between USMLE scores and a resident’s likelihood of successfully passing board examinations [12,13], especially on the first attempt [14,15]. On the other hand, USMLE scores tend to not be as strongly correlated with more subjective outcome measures, such as supervisor and faculty evaluations [10,11,15].…”
Section: Introductionmentioning
confidence: 99%
“…A recent metaanalysis of factors showed that examination-based selection strategies (eg, USMLE Step 1) had a strong positive association with in-service training examinations, whereas medical school grades had a less robust association with subjective outcomes such as resident performance evaluations. 7 USMLE Part 1 may even have a negative correlation with future clinical performance and professionalism. 8 Attributes such as leadership and professionalism are not assessable through standardized testing, but may be evident in a review of the curriculum vitae, personal statement, dean's letter, and letters of recommendation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, medical school grades had a less vigorous association with resident performance evaluations. 14 Other studies have shown that medical school performance does not predict the quality and performance of a resident. [16][17][18] In Brother's article, the USMLE Step 1 score actually suggested a negative correlation with future clinical performance and professionalism.…”
Section: Introductionmentioning
confidence: 99%